Flow‐Based Synthesis of Gold‐Coated Magnetic Nanoparticles for Magnetoplasmonic Sensing Applications. (17th June 2022) - Mehdipour, Milad; Gloag, Lucy; Hagness, Daniel; Lian, Jiaxin; Alam, Md Saiful; Chen, Xueqian; Tilley, Richard D.; Gooding, John Justin
Abstract: Gold‐coated magnetic nanoparticles are key materials for the fast separation and ultrasensitive detection of analytes in magnetoplasmonic sensors. However, the synthesis of gold‐coated magnetic nanoparticles typically requires small‐scale, colloidal methods over hours or days and often results in incomplete shells with variable optical properties. A robust, rapid, and scalable synthesis method is still needed to reliably form a complete gold nanoshell around magnetic nanoparticles. Herein, a new methodology for the synthesis of gold‐coated magnetic nanoparticles via a flow‐based manufacturing system that can easily be scaled up is presented. The developed method first produces gold‐seeded silica coated magnetic nanoparticles and then a complete, tunable gold shell with relatively uniform size and shape. The flow‐based method can be performed in a total time of less than 2 min, enabling rapid and complete gold coating. The particles show both excellent magnetic and plasmonic properties, which facilitates application as biosensing agents in dark‐field microscopy and surface‐enhanced Raman scattering. Abstract : A flow‐based system is presented for the rapid formation of complete gold shells on nanoparticles. The method is shown to be effective for gold‐coating magnetic nanoparticles with controlled magnetoplasmonic properties. The method produces nanoparticles that can be successfully used in biomolecular sensing applications. A rapid and effective gold‐coating method using a flow‐based system is effective for producing nanoparticles with controlled magneto‐plasmonic properties.